Effects of Sub-lethal Irradiation on Patterns of Engraftment after Murine Bone Marrow Transplantation - Andrade, Jacob (2010)
Attempts to reduce the toxicity of hematopoietic stem cell transplantation have led to the use of a variety of immunosuppressive yet non-myeloablative preparative regimens that often include low dose irradiation. To determine the effects of low dose irradiation on the dynamics of donor cell engraftment after bone marrow transplantation (BMT), we coupled standard end-point flow cytometric analysis with in vivo longitudinal bioluminescence imaging performed throughout the early (<10 days) and late (days 10–90) post transplant period. To exclude the contribution of irradiation on reducing immunological rejection, severely immune deficient mice were chosen as recipients of allogeneic bone marrow. Flow cytometric analysis showed that sub-lethal doses of total body irradiation (TBI) significantly increased long-term (14 weeks) donor chimerism in the bone marrow compared to non-irradiated recipients (p<0.05). Bioluminescence imaging demonstrated that the effect of TBI (p<0.001) on chimerism was seen only after the first 7 days post BMT. Flow cytometry analysis at Day 3 showed no increase in the number of donor cells in irradiated BM, confirming that sub-lethal irradiation does not enhance marrow chimerism early after transplantation. Local irradiation also significantly increased late (but not early) donor chimerism in the irradiated limb. Intra-femoral injection of donor cells provided efficient early chimerism in the injected limb, but long-term systemic donor chimerism was highest with intravenous (IV) administration (p<0.05). Overall, the combination of TBI and IV administration of donor cells provided the highest levels of long-term donor chimerism in the marrow space. These findings suggest that the major effect of sub-lethal irradiation is to enhance long-term donor chimerism by inducing proliferative signals after the initial phase of homing.